THU0041 Distinct effects of tnfalpha blockade from tnfalpha and ltalpha blockade in a primate model of subcutaneous abscess formation. (1st June 2001) - Song, XR; Fox, F; Gallo, MA; Rosenberg, A; Jordan, R; Wagner, C
Abstract : Background: TNFα exerts both physiologic and pathologic effects in response to infection conferring the benefit of host defense against infection at the risk of eliciting severe pathology if the response is excessive or inappropriate. Objectives: To examine whether the currently used anti-TNF therapy would affect the innate response to infections in an animal model of subcutaneous abscess formation. Methods: Cynomolgus monkeys were randomly assigned to three treatment groups (saline, etanercept, and anti-TNFα Mab) by body weight and each group contained two male and two female monkeys. Abscess formation was induced with subcutaneous inoculation of Staphylococcus aureus . Results: Intravenous administration of anti-TNFα Mab on days -7, -3, 1, and 4 delayed the onset and reduced the incidence and the severity of S. aureus -induced abscess formation as compared with the saline-treated group at both 10 9 and 10 10 CFU/ml of bacterial inocula given on day 1. Incontrast, no improvement in subcutaneous abscess formation as measured by swelling scores was observed in the receptor construct-treated animals as compared with the saline-treated animals when delivered with the same regimen at the same doses as anti-TNFα Mab. Rather, treatment with receptor construct resulted in a modest increase in the incidence and severity of abscess formation with inocula of 10 9 and 10 10 CFU/ml. Conclusion: Our results provide the initial evidence that a specific anti-TNFα monoclonal antibody therapy administered at 3 mg/kg provides a beneficial effect against S. aureus -induced infection as shown in this non-human primate model of abscess formation.